Práctica reflexiva del profesorado en formación de la carrera de Historia, Geografía y Ciencias Sociales de la Pontificia Universidad Católica de Valparaíso - Peña Hurtado, Cinthia (European Public & Social Innovation Review, 2024)
Introduction: The objective of the research is to identify what type of reflection the pre-services teachers in the History, Geography and Social Sciences program at the Pontifical Catholic University of Valparaíso develop at the end of their professional practice, in order to recognize challenges and training opportunities for the promotion of reflective practice. Methodology: Qualitative descriptive research that analyzed the performances of 33 pre-service teachers in their reflection protocol, identifying the type of reflection carried out: descriptive, comparative or critical. Results: The majority pre-service teachers, when evaluating the impact of their teaching, based on their students' learning and reflecting pedagogically, develop a descriptive reflection, to the detriment of a comparative and critical one. When it is requested to analyze the impact of pedagogical practice from the opinions of the students, this is of the comparative type. Discussions: Systematic reflection on educational practice constitutes a possibility for the formation of teaching identity. Conclusions: It is important to understand reflective practice as a key competence of teaching practice, which is consolidated as a space for continuous learning and reflection par excellence due to its approach and experience of teaching work.